Control de hongos fitopatogenos del suelo en semilleros de tabaco con Trichoderma Harzianum - Stefanova, M.=700 1 Sandoval, I.; Martinez, M.L.; Heredia, I.; Ariosa, M.D.; Arevalo, R.
(Es, En)
Ilus., 3 ref
Keywords: NICOTIANA TABACUM; HONGOS ENTOMOPATOGENOS; HONGOS DEL SUELO; SEMILLEROS; CONTROL BIOLOGICO; TRICHODERMA HARZIANUM; CUBA